Robust Visual Responses and Normal Retinotopy in Primate Lateral Geniculate Nucleus following Long-term Lesions of Striate Cortex - Yu, Hsin-Hao; Atapour, Nafiseh; Chaplin, Tristan A.; Worthy, Katrina H.; Rosa, Marcello G.P. (The Journal of neuroscience, 2018)
Lesions of striate cortex (V1) trigger massive retrograde degeneration of neurons in the LGN. In primates, these lesions also lead to scotomas, within which conscious vision is abolished. Mediation of residual visual capacity within these regions (blindsight) has been traditionally attributed to an indirect visual pathway to the extrastriate cortex, which involves the superior colliculus and pulvinar complex. However, recent studies have suggested that preservation of the LGN is critical for behavioral evidence of blindsight, raising the question of what type of visual information is channeled by remaining neurons in this structure. A possible contribution of LGN neurons to blindsight is predicated on two conditions: that the neurons that survive degeneration remain visually responsive, and that their receptive fields continue to represent the region of the visual field inside the scotoma. We tested these conditions in male and female marmoset monkeys ( Callithrix jacchus ) with partial V1 lesions at three developmental stages (early postnatal life, young adulthood, old age), followed by long recovery periods. In all cases, recordings from the degenerated LGN revealed neurons with well-formed receptive fields throughout the scotoma. The responses were consistent and robust, and followed the expected eye dominance and retinotopy observed in the normal LGN. The responses had short latencies and preceded those of neurons recorded in the extrastriate middle temporal area. These findings suggest that the pathway that links LGN neurons to the extrastriate cortex is physiologically viable and can support residual vision in animals with V1 lesions incurred at various ages. SIGNIFICANCE STATEMENT Patients with a lesion of the primary visual cortex (V1) can retain certain visually mediated behaviors, particularly if the lesion occurs early in life. This phenomenon (“blindsight”) not only sheds light on the nature of consciousness, but also has implications for studies of brain circuitry, development, and plasticity. However, the pathways that mediate blindsight have been the subject of debate. Recent studies suggest that projections from the LGN might be critical, but this finding is puzzling given that the lesions causes severe cell death in the LGN. Here we demonstrate in monkeys that the surviving LGN neurons retain a remarkable level of visual function and could therefore be the source of the visual information that supports blindsight.